O conceito de História em Voltaire - Zaninetti, Priscila Aragão (Universidade Federal de São Carlos, 2018)
The purpose of this dissertation is to study the concept of history in Voltaire. Therefore the research embraces the conception of historical narration, the methodological resources established to verify them, and also the discipline that entitles the work that, here, will be central, The Philosophy of History. It covers such areas, however, with a specific question that would interweave them, namely the possible conservation of contents from the historical conception of Antiquity and the elaboration of contents concerning the historical conception of Modernity by the Voltairean concept of history. Thus narrativity, linked to the adoption of the principle of verisimilitude, and conviction in the instructive utility of history, would therefore be contents that would refer back to the old sense of the concept of history. However, in Voltaire, the separation between the true historical account and the fable aims not only at the education of princes, but above all the progress of the human spirit. Moreover, the Voltairean concept of history seems structured by the specifically historical temporality, capable of encompassing the multiplicity of human manifestations and, therefore, the development of customs by various peoples throughout the centuries. Under these terms, such a concept would also contain contents elaborated by the historiography of Modernity, at which time the philosopher had belonged and for which he had contributed much to the elaboration of his intellectual apparatus. That said, the hypothesis of this dissertation is to understand the supposed ambivalence of the Voltairean concept of history, placing it between the meanings of the historical conceptions of Antiquity and Modernity, as the intersection between inheritance and acquisition, as the perfection of the corpus of thought bequeathed by tradition for a rationality that would experience the social, political, economic and cultural changes of Modernity, thus constituting its own historical thought.
Keywords: História; Narrativa; Filosofia da história; Progresso; Voltaire; History; Narrativity; Philosophy of History; Progress; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA